Characterizing near‐surface firn using the scattered signal component of the glacier surface return from airborne radio‐echo sounding. Issue 24 (30th December 2016) - Rutishauser, Anja; Grima, Cyril; Sharp, Martin; Blankenship, Donald D.; Young, Duncan A.; Cawkwell, Fiona; Dowdeswell, Julian A.
Abstract: We derive the scattered component (hereafter referred to as the incoherent component) of glacier surface echoes from airborne radio‐echo sounding measurements over Devon Ice Cap, Arctic Canada, and compare the scattering distribution to firn stratigraphy observations from ground‐based radar data. Low scattering correlates to laterally homogeneous firn above 1800 m elevation containing thin, flat, and continuous ice layers and below 1200 m elevation where firn predominantly consists of ice. Increased scattering between elevations of 1200–1800 m corresponds to firn with inhomogeneous, undulating ice layers. No correlation was found to surface roughness and its theoretical incoherent backscattering values. This indicates that the scattering component is mainly influenced by the near‐surface firn stratigraphy, whereas surface roughness effects are minor. Our results suggest that analyzing the scattered signal component of glacier surface echoes is a promising approach to characterize the spatial heterogeneity of firn that is affected by melting and refreezing processes. Key Points: Scattering component of airborne radio‐echo sounding surface echo is mapped across Devon Ice Cap The scattering signal component is mainly affected by the near‐surface firn stratigraphy Effects from surface roughness on the scattering component are minor